2021
DOI: 10.1088/1755-1315/744/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton diversity in Lake Tondano, Indonesia

Abstract: Study on freshwater ecology have been long focused on subtropical habitats with few references to tropical regions including Indonesia. Zooplankton, in particular, is an important component of aquatic ecosystem as they are key player of aquatic food webs, thus a solid understanding of their community structure can be of direct benefit to freshwater ecosystem management. The spatial patterns of zooplankton diversity in Lake Tondano, Celebes Island – Indonesia were studies in 2013, with the main aim was to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
1
2
Order By: Relevance
“…L −1 ) but diversity (H' = 2.2 ± 0.0) was significantly higher (p < 0.05) compared to artificial lakes. Zooplankton diversity recorded in this study was higher compared to the zooplankton diversity in Tondano Lake, Indonesia (H' = 1.73-1.85) [41], and in several urban lakes in Malaysia (H' = 1.41-2.34) [22]. However, zooplankton diversity was low compared to the zooplankton diversity in Ulansuhai Lake, China (H' = 2.75) [17].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…L −1 ) but diversity (H' = 2.2 ± 0.0) was significantly higher (p < 0.05) compared to artificial lakes. Zooplankton diversity recorded in this study was higher compared to the zooplankton diversity in Tondano Lake, Indonesia (H' = 1.73-1.85) [41], and in several urban lakes in Malaysia (H' = 1.41-2.34) [22]. However, zooplankton diversity was low compared to the zooplankton diversity in Ulansuhai Lake, China (H' = 2.75) [17].…”
Section: Discussioncontrasting
confidence: 70%
“…The number of zooplankton species recorded in this study was higher compared to the 45 zooplankton species found by Abd Razak and Sharip [22] and the 49 zooplankton species reported by Ismail et al [40] in Malaysian lakes. However, the number of zooplankton species obtained in this study was lower compared to the 112 zooplankton species in Tondano Lake, Indonesia [41], and the 65 zooplankton species in Baiyangdian Lake, China [42]. Rotifers, in general, represent the main contributors to the zooplankton density and diversity in freshwater ecosystems [7,43,44].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation